Epidemiology of HIV-assosiated tuberculosis in the Far Eastern Federal District - E. A. Bazykina; O. E. Trotsenko; V. B. Turkutyukov; L. A. Balakhontseva; V. O. Kotova (Journal of microbiology epidemiology immunobiology, 2019)
Aim. To determine epidemiologic manifestations of HIV-infection associated with tuberculosis in the Far Eastern Federal District (FEFD). Materials and methods. The retrospective epidemiologic analysis was performed based on the official statistical data form № 61 «Data on HIV infected population» in reference to clinically registered HIV and tuberculosis co-infected patients. Results. The research revealed a growth trend of general tuberculosis prevalence against the background of stabilization of the tuberculosis incidence in HIV-positive patients in the FEFD during 2006-2015. High tuberculosis-burden was registered in the most of the Far Eastern federal district constituent entities (Khabarovsk and Primorsky regions, Jewish and Chukotka autonomous districts, Amursk oblast, and Republic Sakha (Yakutia). A statistically significant positive correlation (r=0,66, p=0,003) between percentage of active tuberculosis in HIV-positive patients and percentage of patients with AIDS was identified. The percentage of active tuberculosis in HIV-positive people on average over 10 years equaled to 65.0%. The prevalence rate of tuberculosis was higher by 19.2% in HIV-positive inmates compared with HIV-positive civilians. Conclusion. Тhe FEFD is a constituent entity of the Russian Federation with high and unstable levels of tuberculosis prevalence in people living with HIV.